Transcriptomic and behavioral studies reveal that glutamate receptors are involved in depressive-like behavior in adult olive flounder Paralichthys olivaceus - Liangfang Liu; Tangsong Feng; Mengmeng Shi; Huafeng Zou; Weiqun Lu (Aquaculture and Fisheries)
Olive flounder (Paralichthys olivaceus), a marine demersal flatfish species, exhibits obvious timid and depressive-like characteristics. Adult olive flounder bury themselves in the sand and present motionless behavior. However, the detail mechanism of regulating the motionless behavior is not fully understood. In this study, using adult group (AG) and juvenile group (JG) flounder as a model, we compared the locomotor activity of AG and JG flounder, and analyzed the transcriptomic expression profiles in the spinal cord by RNA-seq methods. The behavioral experiment showed that AG flounder displayed lower locomotor activity. Transcriptome analysis found a total of 1711 significantly differential expressed genes (DEGs), among which 818 genes were up-regulated and 893 genes were down-regulated in AG flounder compared with JG flounder. Specifically, locomotor behavior related genes (parvalbumin, urotensin II and creatine kinase) were down-regulated. Meanwhile glial fibrillary acidic protein, the biomarkers of astroglial pathology, and glutamatergic synaptic genes were significantly up-regulated in AG flounder. In addition, Gene Ontology (GO) enrichment analysis revealed that DEGs enriched in peptide biosynthetic process, translation procession were down-regulated in the AG flounder. The Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis revealed that ribosome, oxidative phosphorylation and glutamatergic synapse pathway were over-represented. After treatment with antagonist of glutamate receptor LY341495, flounder more often swam out of the sand and displayed significantly more off-bottom swimming behavior, suggesting the anti-depressive effect of LY341495. Taken together, in combination with behavioral tests and transcriptomic analyses, we conclude that the glutamate receptor in spinal cord plays an important role in timid and depressive-like behavior in flounder.